Factors Influencing the Purchase Decision of Goat Milk Powder at Indo Natural Farm - Putri, Salsabila Hana; Aziz Husyairi, Khoirul (Jurnal Sosial Terapan, 2024)
This study aims to analyze the factors influencing purchase decisions and marketing strategies of goat milk powder at Indo Natural Farm. The research method used is quantitative, employing descriptive analysis, factor analysis, SWOT analysis, and IFAS and EFAS analysis. The factors analyzed include purchase decisions and the 4Ps marketing mix. The results show that factors such as product, price, promotion, place, and purchasing decisions have a significant impact on customer purchasing decisions. Additionally, SWOT, IFAS, and EFAS analyses provide insights into the company’s position in the industry, as well as the opportunities and challenges it faces. Based on the factor analysis, seven factors were identified: product quality, information access and health, promotion and incentives, product information and value, product appeal and place, price, and accessibility and promotion. Based on the IFAS and EFAS scores, goat milk powder at Indo Natural Farm is positioned in quadrant II and is recommended to implement a diversification strategy. Keywords: Goat Milk Powder, Purchase Decisions, Marketing Strategy